The impact of the CervicalCheck controversy on provision of colposcopy services in Ireland: A cohort study. (July 2021) - Cheung, Maria; Fitzpatrick, Myra
Highlights: Controversy around cancer screening can cause anxiety in public & clinicians. Increased colposcopy referral by GP for suspicious cervix seen following controversy. Anxiety in colposcopists also; increase in colposcopic opinion of CIN. Resulting histology; increase in low-risk CIN1, but no increase in high-risk changes. Distrust & anxiety after controversy can have negative effects on healthcare for all. Abstract: Objectives: In 2018, an inquiry into the Irish Cervical Cancer screening programme (CervicalCheck) was initiated, following publicised cases of non-disclosure regarding internal audit results of cytology screening in women diagnosed with cervical cancer. The inquiry attracted widespread media coverage and the government offered women free, out of programme screening. We investigated whether the controversy led to an increase in referrals based on clinical suspicion and the impact on waiting times for abnormal cytology. Study design: A retrospective cross-sectional analysis was performed, including all colposcopy referrals to The National Maternity Hospital, Dublin, before (March 2016–2018) and after (March 2018–2020) the media coverage. Chi-squared (χ2) and independent one-tailed t-tests were used to perform between-group analyses. Results: Post-controversy, suspicious cervix referrals increased (10.1 %–14.2 %; p = 0.037 × 10 −27 ), as did colposcopic impression of CIN (p = 0.000000016). While an increase in CIN1 histology (18.5 %–30.3 %) was diagnosed, a decrease in high-risk CIN2 (10 % to 8.6 %), CIN3 (6.2 % to 2.9 %), AIS (1.2 % to 0.3 %) and invasive cancer (2.8 % to 1.2 %; p = 0.0058 × 10 −9 ) were diagnosed. Across all grades of cytological abnormality, significantly fewer patients were reviewed in the recommended waiting time post-controversy. Half of delayed abnormal cytology referrals had high-grade changes. Conclusions: This study highlights the profound impact that the CervicalCheck Controversy had on the women attending colposcopy and clinicians performing the screening tests, and the direct impact on women with confirmed cytological abnormalities. The increase in suspicious cervix referrals reflects a lack of confidence in both clinical practice and screening test results. The importance of public trust in the effective delivery of screening services cannot be ignored. Increased resources are required to ensure all women are seen within recommended time frames. Heightened anxiety and increased surveillance does not necessarily lead to better clinical outcomes for patients but can result in unnecessary distress for low-risk patients and delays to diagnosis for high-risk patients with concerning abnormalities.